In Vitro and In Vivo Comparative Evaluation of a Shellac-Ammonium Paclitaxel-Coated Balloon versus a Benchmark Device - Congying Xia; Yunhan Jiang; Shuangshuang Li; Dan Xiong; Xiaojie Chen; Yufang Chen (Journal of Interventional Cardiology)
Objectives. The present study was designed to compare the characteristics and performance regarding drug delivery of a novel drug-coated balloon (DCB) to a benchmark device (Restore® versus SeQuent® Please) in an in vitro and in vivo model. Background. Although Restore® and SeQuent® are both paclitaxel-coated, they use different coating excipient, shellac-ammonium salt and iopromide, respectively. Preclinical study comparing these two different commercial DCBs regarding their characteristics and effects on early vascular response is sparse. Methods. Restore® and SeQuent® DCBs were scanned with electron microscopy for surface characteristic assessment. Both DCBs were transported in an in vitro vessel model for the evaluation of drug wash-off rate and particulate formation. Eighteen coronary angioplasties with either Restore® or SeQuent® DCBs were conducted in 6 swine (three coronary vessels each). Histopathological images of each vessel were evaluated for vessel injury. Results. The surface of Restore® DCB was smooth and evenly distributed with hardly visible crystal, while SeQuent® DCB showed a rougher surface with relatively larger apparent crystals. Restore® DCB had a lower drug wash-off rate and fewer large visible particles, compared to the SeQuent® DCB. No significant difference in mean injure score was found between Restore® and SeQuent® group. Conclusion. Our results suggest that Restore® is better in preclinical performance regarding less release of particles and lower drug wash-off rate as compared to SeQuent® Please. The Restore® DCB, using stable amorphous coating and shellac-ammonium salt as an excipient, appears to provide an advantage in drug delivery efficacy; however, further clinical studies are warranted.